2021
DOI: 10.31681/jetol.907470
|View full text |Cite
|
Sign up to set email alerts
|

What do secondary school students think about experimental practices in science lessons taught in distance education?

Abstract: Following the COVID-19 pandemic, which took the world under its influence, many countries, including our country, switched to distance education. During this period, students did not go to schools and lessons continued to be taught online remotely. In this study, it was aimed to investigate secondary school students' opinions about conducting experiments in science lessons in the distance education process. The study group consisted of 587 secondary school students receiving education in 24 schools located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…54 Many experts in the field agree that active teaching strategies are of significant help for the improvement of conceptual learning of the different subjects addressed both at university and secondary level. [55][56][57][58] Active learning methodologies, a product of the last 30 years of educational research, significantly improve the conceptual understanding of physics, 59,60 reproducing the scientific process in the classroom and aiding the development of reasoning skills. Therefore, various authors and international organizations have proposed methodologies and strategies to increase student achievement and motivation, always highlighting the use of experimental resources and experimentation in teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Many experts in the field agree that active teaching strategies are of significant help for the improvement of conceptual learning of the different subjects addressed both at university and secondary level. [55][56][57][58] Active learning methodologies, a product of the last 30 years of educational research, significantly improve the conceptual understanding of physics, 59,60 reproducing the scientific process in the classroom and aiding the development of reasoning skills. Therefore, various authors and international organizations have proposed methodologies and strategies to increase student achievement and motivation, always highlighting the use of experimental resources and experimentation in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Learning physics requires bringing concepts and models to the classroom, but also introducing pupils to the development of some specific aspects of scientific work, to ensure satisfactory learning by students 54 . Many experts in the field agree that active teaching strategies are of significant help for the improvement of conceptual learning of the different subjects addressed both at university and secondary level 55–58 . Active learning methodologies, a product of the last 30 years of educational research, significantly improve the conceptual understanding of physics, 59,60 reproducing the scientific process in the classroom and aiding the development of reasoning skills.…”
Section: Introductionmentioning
confidence: 99%
“…However, being unable to experiment was a significant shortcoming for them. Bostan Sarıoğlan et al (2021), in their study with secondary school students, found that the most common answer among students' expectations from distance education is to increase experimental practices, and they felt face-toface experimentation more effective than distance education.…”
Section: Introductionmentioning
confidence: 99%
“…It is stated that the benefits of distance education are that students and teachers can participate in educational activities from anywhere, and this saves time and reduces the cost of education (Benzer & Akkaya, 2021;Moore & Kearsley, 2011). The limitations of distance education are listed as the inability of every student to have equal access to distance education and the inability to get enough efficiency from the lessons as a result of not providing active communication (Bostan Sarıoğlan, Şen & Altaş, 2021;Can, 2020;Çağlar, 2010). Distance education, which is widely used in the Covid-19 period, has also caused learning losses in students (Donnelly & Patrinos, 2021;Timmons et al, 2021;Zhdanov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%